Introducing an Eco-ELT-Based Learning Model for Pragmatics in English Education: A Sustainable Approach to Teaching Language Use - Hasanul Misbah (Attractive : Innovative Education Journal, 2024)
This article presents an Eco-ELT-based learning model for the Pragmatics course in English Education, drawing on the Eco-ELT framework. This innovative model integrates ecological principles with the study of Pragmatics, aiming to enhance the understanding of language use in context and foster a deeper connection between students and their environment. The article introduces several relevant learning materials, effective teaching methods, and assessment strategies aligned with the Eco-ELT approach. By emphasizing context, social responsibility, and sustainability, this model promotes a more comprehensive and context-aware approach to teaching Pragmatics in English Education. By integrating ecological principles into the study of language use in context, this model offers students a deeper understanding of how language operates in the real world, shaped by both social and ecological factors. Through relevant learning materials, innovative teaching methods, and comprehensive assessments, this model encourages students to use language responsibly and effectively, fostering critical thinking and social awareness.